Zum Verhältnis zwischen Präsens und Futur im Litauischen: Präliminaria im Bereich sprechzeitenthobener Propositionen - Wiemer, Björn (Vilnius University Open Series, 2021)
The article examines non-deictic uses of present and future tense in Lithuanian. Narrative use, in which reference intervals match with singular events, is distinguished from suspended propositions characterized by lack of such reference intervals (habitual, dispositional and circumstantial modal, and conditional meanings). Present tense is frequently involved in both usage domains, while the future is rare in narrative use, but overlaps with present tense in certain types of suspended propositions. Moreover, its temporal-deictic use is inherently associated with suspended propositions and “linked” to them via epistemic implicatures. This, in contrast to the present, makes the future more likely to be employed in predictions which entail an observer. The analysis is supplemented by a brief comparison with non-deictic tense use in the nonpast-domain of Slavic languages, yielding a grid of criteria that should be used in crosslinguistic studies on tense-aspect systems based on stem derivation and the feature [±bounded].